2012
DOI: 10.1186/1471-2377-12-158
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic risks of recombinant factor VIIa Use in warfarin-associated intracranial hemorrhage: a case–control study

Abstract: BackgroundRecombinant factor VIIa (rFVIIa) may be used for rapid hemostasis in life-threatening hemorrhage. In warfarin-associated intracerebral hemorrhage (wICH), FVIIa use is controversial and may carry significant thromboembolic risks. We compared incidence of baseline thromboembolic risk factors and thromboembolism rates in wICH patients treated with additional rFVIIa to those treated with standard therapy of fresh frozen plasma (FFP) and vitamin K alone.MethodsWe identified 45 consecutive wICH patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(25 reference statements)
1
2
0
2
Order By: Relevance
“…It also showed that the INR reversal comes with no significant risk of thromboembolic complications. This conclusion is corroborated by other studies that have also investigated the safety of rFVIIa for warfarin patients (Deveras and Kessler 2002 ; DeLoughery et al 2013 ; H-Y et al 2012 ). To our knowledge, this is one the largest retrospective reviews looking specifically at the use of rFVIIa administration for patients in need of emergent neurosurgical intervention.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…It also showed that the INR reversal comes with no significant risk of thromboembolic complications. This conclusion is corroborated by other studies that have also investigated the safety of rFVIIa for warfarin patients (Deveras and Kessler 2002 ; DeLoughery et al 2013 ; H-Y et al 2012 ). To our knowledge, this is one the largest retrospective reviews looking specifically at the use of rFVIIa administration for patients in need of emergent neurosurgical intervention.…”
Section: Discussionsupporting
confidence: 78%
“…rFVIIa is known to rapidly normalize INR in warfarin-associated systemic bleeding but whether such INR normalization reflects full reversal of coagulopathy remains controversial (H-Y et al 2012). Twenty percent of patients in our study received a dose of rFVIIa less than 50 mcg/kg which is considered low dosing of rFVIIa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Связаны они, прежде всего, с его основным эффектом -генерацией «тромбинового взрыва» в месте повреждения сосудистой стенки, т.е. относятся к тромботическим [87,88]. Анализ этой проблемы показал, что, действительно, клиническое применение rFVIIa связано с повышенным риском тромботических осложнений у пациентов вне ситуации массивной кровопотери и выраженной гипокоагуляции (ЧМТ, ВМК).…”
unclassified
“…Анализ этой проблемы показал, что, действительно, клиническое применение rFVIIa связано с повышенным риском тромботических осложнений у пациентов вне ситуации массивной кровопотери и выраженной гипокоагуляции (ЧМТ, ВМК). При этом на фоне применения препарата возрастает, главным образом, частота артериальных, а не венозных тромбозов, а основным контингентом являются пациенты старше 70 лет [87][88][89]. Исходя из механизма действия rFVIIa, который реализуется только в месте контакта с тканевым фактором (т.е.…”
unclassified